Designing an Advanced Biosensor for Rapid Analysis and Detection of Blood Components - Farida. Kebaili; Ahlam. Harhouz; Abdesselam. Hocini (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract In this study, we propose a novel biosensor based on a hexagonal-shaped microcavity with two slot waveguides within a two-dimensional photonic crystal. The biosensor aims to detect various blood components by utilizing a refractive index measurement. The device operates in the TM-polarized light wavelength range of 1150-1880 nm. It consists of two slot waveguides coupled with a hexagonal-shaped microcavity, formed by removing seven lattice holes. The microcavity is separated from the waveguides by two holes. When the analyte infiltrates the cavity, it induces a change in refractive index, leading to a wavelength shift at the output terminal. The proposed design achieves a high sensitivity of over 687.496 nm/RIU. The simulation of the proposed design is performed using both the Plane Wave Expansion (PWE) method and the Finite-Difference Time-Domain (FDTD) algorithm. The results demonstrate that the slot waveguide configuration provides excellent transmission.